PROBABILITAS PERBAIKAN STATUS GIZI ANAK BALITA GIZI BURUK PENGUNJUNG KLINIK GIZI PUSLITBANG GIZI BOGOR SEBELUM DAN PADA SAAT KRISIS EKONOMI - Sihadi Sihadi; Sri Muljati; Amelia Amelia; Susi Suwarti Suwardi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2001)
Probability of Children Severe Malnutrition Improvement on Out-Patient Rehabilitation of Nutrition Clinics In Puslitbang Gizi Bogor at Before and After Economic Crisis.Background: The nutrition clinic of Puslitbang Gizi, Bogor provides a out-patient rehabilitation care package for severely malnourished children during six months. The clinical care is merely aimed at the family itself at home. Due to the changed in economic situation, it is presumed that there will be a difference in nutrition improvement during the crisis as compared to before the crisis.Objective: The objective of the study is to evaluate the effect of out-patient rehabilitation care package by the nutrition clinic of Puslitbang Gizi, Bogor on the improvement of severely malnourished children before and during economic crisis.Methods: The study was conducted using retrospective data of out-patient provided with the rehabilitation care package by the nutrition clinic. Out-patients visiting the nutrition clinic during 1990-1997 represented the "before crisis group", and Out-patients during 1998-1999 the "during crisis group". Nutritional status was expressed in Z-score for "weight for age" and "weight for height", based on WHO-NCHS standards. The cut off point for severe malnutrition is below - 3 SD of the reference.Results: Based on background of children for sex, age group, birth sequence, number of survival child, education level of father and mother to the group of before and during the economic crisis showed no significant different (p>0.05). Type of malnutrition of the groups before and during the crisis showed significant different (p>0.05). Percentage of malnutrition type with the clinical symptoms in the group of before economic crisis is higher than during the economic crisis. Probability of improvement from severe to moderate malnutrition using Z-score index of weight for age and weight for height indicated no significant difference on rehabilitation of out-patient during 6 months package care between before and during the economic crisis (p>0.05).Keywords: underfive years old, severe malnutrition, nutritional status improvement, economic crisis.